Managing Macrophomina phaseolina causing dry root rot of legumes by a native strain of Bacillus firmus - P.K. CHAKARBARTY AND BHAGWAN SINGH, SATISH LODHA*, RITU MAWAR (Indian Phytopathology, 2013)
Bacillus firmus, a bacterium, isolated from Brassica residue amended soil was found antagonistic to Macrophomina phaseolina (Tassi) Goid., a soil borne plant pathogen, causing charcoal rot on legumes. In dual culture tests, a scarlet pigmentation developed after the interaction of both the organisms. A cell free zone from this pigmentation also inhibited pathogen suggesting release of some antibiotic, but the reduction in mycelial growth of M. phaseolina was significantly higher in presence of B. firmus than its cell free filtrate. The bacterium could not inhibit growth of most prevalent soil fungi of the arid region including Trichoderma harzianum, which shows that probably this strain of B. firmus is a specific antagonist to Macrophomina. Increased growth and nodulation in B. firmus coated compared to uncoated seedlings of guar (Cyamopsis tetragonoloba (L.) Taub.) indicated its ability to promote plant growth. The effectiveness of B. firmus coated seeds was successfully demonstrated at growers’ field. This appears to be the first record of a new bio control agent against M. phaseolina.